Fitness prison officers penitentiary in Bydgoszcz Fordon - Chabros, Małgorzata; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
The aim of the study was to determine the degree of physical fitness characterized by prison officers. The study was conducted among officers of the Prison Service Prison in Bydgoszcz - Fordon. Studied 195 people (24 women and 171 men). Conclusions: (1) Officers of the Prison Service Prison in Bydgoszcz - Fordon has a very good level of physical fitness, (2) Most women differ from men strength, while most similar results were obtained in the test agility, (3) The best developed among women is agility and power, while in men the strength prevails.